Three chlorotoluene-degrading bacterial strains: Differences in biodegradation potential and cell surface properties. (December 2019) - Smułek, Wojciech; Cybulski, Zefiryn; Guzik, Urszula; Jesionowski, Teofil; Kaczorek, Ewa
Abstract: Pollution of the environment with chlorinated aromatic compounds is a problem of increasing importance, which has stimulated the search for efficient methods for the remediation of contaminated soil and water. Additionally, for better understanding of the significance of bioavailability to biodegradation, investigation of the cell surface properties is necessary. Hence, this study concerns the properties and possible application, in chlorotoluene removal, of three newly isolated environmental bacterial strains from the genera Pseudomonas, Raoultella and Rahnella . The results show the differences in the biochemical profiles of the isolated strains, their cellular fatty acid composition and their hemolytic properties. However, all three strains exhibit high biodegradation potential, degrading not less than 60% of each monochlorotoluene isomer in 21-day experiments. What is more, observations of changes in the cell surface properties indicate the possible adaptation mechanisms of the strains that enable efficient biodegradation of hydrophobic pollutants such as monochlorotoluenes. Graphical abstract: Image 1 Highlights: Newly-isolated bacterial strains are efficient chlorotoluenes-degraders Changes in the cell surface properties indicated the strains adaptation mechanisms The isolated strains differed significantly in the cellular fatty acids profile The studied strains have a great potential to be used in the chlorotoluenes removal